Understanding species persistence for defining conservation actions: A management landscape for jaguars in the Atlantic Forest - de Angelo, Carlos Daniel (2013)
Habitat models constitute useful instruments for understanding species-habitat interactions and can constitute helpful conservation tools. The Upper Paraná Atlantic Forest (UPAF) of South America still holds the world’s southernmost jaguar (Panthera onca) population. Our aims were: (i) to test several a priori hypotheses on the factors affecting jaguar persistence in this region, (ii) to map habitat suitability and identify areas with potentially conflicting habitat conditions, and (iii) to identify priority areas for management and improve the conservation initiatives for jaguars and the UPAF. Following an information-theoretic approach, we used presence records of jaguars and pseudo-absences in generalized linear models. We structured hypotheses into two groups which demand different management actions: land cover and human persecution. The best model of each group was used to develop a two-dimensional habitat model. Jaguar persistence was favoured by current and historical native forest cover, and hindered by human land uses. Protection favoured jaguar presence whereas human accessibility and high human population density had negative effects. The two-dimensional model suggests that <8% (20,670 km2) of the landscape represents potential core areas for jaguars (good land-cover characteristics and low human persecution) and 11.8% (32,563 km2) stands as potentially attractive sinks where good land-cover conditions conflict with high human persecution. Reduction of human persecution is urgently needed to increase the core areas for jaguars in this region, but improvement of land-cover conditions is important for sustaining the connectivity among jaguar populations that seem to be isolated in different areas of the UPAF.